Integrated optics prototype beam combiner for long baseline interferometry in the L and M bands - Tepper, J.; Labadie, L.; Diener, R.; Minardi, S.; Pott, J. -U.; Thomson, Robert; Nolte, Stefan (Astronomy & Astrophysics, 2017)
Context. Optical long baseline interferometry is a unique way to study astronomical objects at milli-arcsecond resolutions not attainable with current single-dish telescopes. Yet, the significance of its scientfic return strongly depends on a dense coverage of the uv-plane and a highly stable transfer function of the interferometric instrument. In the last few years, integrated optics (IO) beam combiners have facilitated the emergence of 4-telescope interferometers such as PIONIER or GRAVITY, boosting the imaging capabilities of the VLTI. However, the spectral range beyond 2.2 μm is not ideally covered by the conventional silica based IO. Here, we consider new laser-written IO prototypes made of gallium lanthanum sulfide (GLS) glass, a material that permits access to the mid-infrared spectral regime. Aims. Our goal is to conduct a full characterization of our mid-IR IO two-telescope coupler in order to measure the performance levels directly relevant for long-baseline interferometry. We focus in particular on the exploitation of the L and M astronomical bands. Methods. We use a dedicated Michelson-interferometer setup to perform Fourier transform spectroscopy on the coupler and measure its broadband interferometric performance. We also analyze the polarization properties of the coupler, the differential dispersion and phase degradation, as well as the modal behavior and the total throughput. Results. We measure broadband interferometric contrasts of 94.9% and 92.1% for unpolarized light in the L and M bands. Spectrally integrated splitting ratios are close to 50%, but show chromatic dependence over the considered bandwidths. Additionally, the phase variation due to the combiner is measured and does not exceed 0.04 rad and 0.07 rad across the L and M band, respectively. The total throughput of the coupler including Fresnel and injection losses from free-space is 25.4%. Furthermore, differential birefringence is low (<0.2 rad), in line with the high contrasts reported for unpolarized light. Conclusions. The laser-written IO GLS prototype combiners prove to be a reliable technological solution with promising performance for mid-infrared long-baseline interferometry. In the next steps, we will consider more advanced optical functions, as well as a fiber-fed input, and we will revise the optical design parameters in order to further enhance the total throughput and achromatic behavior.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Instrumentation: high angular resolution; Instrumentation: interferometers; Techniques: interferometric